Some aspects of magnetosphere–ionosphere relations. (June 2015) - Petrukovich, A A; Mogilevsky, M M; Chernyshov, A A; Shklyar, D R
Abstract: This paper reviews the characteristics of plasma-wave perturbations produced by wave-particle interactions in the magnetosphere–ionosphere system. These perturbations may, notably, be due to lightning discharges and to radiation from high-power low-frequency transmitters. These can form waveguide channels, i.e., density inhomogeneities, which originate in the ionosphere above the radiation source and extend along geomagnetic field lines in the magnetosphere. Although different in nature, the natural and man-made radiation sources may have similar effects on processes in the circumterrestrial plasma, causing the excitation of a variety of emissions in it and stimulating the precipitation of charged particles from the magnetosphere into the ionosphere.